Iste Ergo Sum. On Mirrors, Materiality and Enunciation - Lobaccaro , Luigi (E|C, 2023)
Starting from Eco’s and Fabbri’s theories on mirror image status, this paper aims to construct a theoretical framework that redefines the intricate relationship between subjectivity, enunciation, and mirror prosthetic status. If we consider the mirror in its material characteristics, it will be possible to state how its first function is space reduplication. This function is possible because the mirror does something to the observing subject, bringing forth possible worlds through the material agency (Malafouris, Koukouti 2022). In this framework, self-image recognition is only one of the possible enunciative relations that mirrors shape and facilitate (Lobaccaro, Bacaro 2021). I will argue that the possibility of recognising one’s own image, is the result of a form of impersonal enunciation that the mirror image opens through its material attributes (Paolucci 2020). The engagement with the reflective surface distributes simulacra that serve as enunciative instances of different kinds: the self, me, you, and the other interchange within the mirror, concealing the catoptric nature of the phenomenon.